A dynamical systems perspective on mediating violence in schools: emergent roles of child and youth care workers - Vanderven, Karen; Torre, Carlos Antonio (Child Care Quarterly, 1999)
In recent years, violence has been a major concern for human service professionals and increasingly, to child and youth care workers particularly as they have served in schools where major violent events have occurred. Most often violence prevention and intervention efforts ignore the systemic aspects of violence and are too narrowly focused. This article proposes that a consideration of violence in schools be based on dynamical systems theory. This theory offers rich possibilities for generating a useful model for mediating school violence and for suggesting ways in which child and youth care workers can use their competencies to address the multiple factors related to school violence. The article includes an overview to the concepts of dynamical systems theory, offers the dynamical systems model for mediating school violence and presents implications for the roles and functions of child and youth workers particularly in the emerging area of school based child and youth care work. © 1999 Human Sciences Press, Inc.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/148-312-108-701-782 tex.type: [object Object]
Keywords: dept.edu